Nienawiść realna czy wymyślona? Relacje między Grekami a Kartagińczykami na Sycylii w czasach Dionizjusza I = Hatred real or invented? Relations between the Greeks and the Carthaginians in Sicily in times of Dionysius I - Dudziński, Andrzej (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article addresses the issue of relations between the Greeks and the Carthaginians in Sicily 410-367 BC. The aim of the article is to reach beyond the open statements of general hostility, present in the literary sources, and to focus on the events described by said sources. First, the anaysis focuses on the seemingly abundant evidence of fear and hate between the Greeks and the Carthaginians.
Keywords: Kartagina; starożytna Sycylia; Dionizjos I (tyran Syrakuz; ok. 430 p.n.e.-367 p.n.e.); Carthage; Ancient Sicily; Dionysius I (c. 430-367 BC)